N '-(4-Methoxy-2-oxidobenzylidene)4-nitrobenzohydrazidato-kappa O-3,N,O ' (pyridine-kappa N)copper(II) - Lair, N.M.; Ng, S.W.; Ali, Hapipah Mohd (International Union of Crystallography, 2009)
The pyridine-coordinated Cu-II atom in the title Schiff base complex, [Cu(C15H11N3O5)(C5H5N)], is O,N,O'-chelated by the doubly deprotonated Schiff base ligand. The metal centre is in a square-planar coordination geometry.